London District Taxi Column of the Home Guard, 1942 (pg. 1) (London, 1942)
1942 1939-1945 "London District Taxi Column of the Home Guard, 1942 (pg. 1)" [HFR0042a], 1942 These hand-written notes describe an exercise carried out by the London District Taxi Column of the Home Guard on 4 October, 1942 in Epping Forest. An edited version of this report appeared in the October 1942 issue of 'The Cab Trade News', published by the Transport and General Workers Union.